Applications of Macrocyclic Host Molecules in Immune Modulation and Therapeutic Delivery - Soni, Shreya S.; Alsasa, Abdulrahman; Rodell, Christopher B. (Frontiers in Chemistry, 2021)
The immune system plays a central role in the development and progression of human disease. Modulation of the immune response is therefore a critical therapeutic target that enables us to approach some of the most vexing problems in medicine today such as obesity, cancer, viral infection, and autoimmunity. Methods of manipulating the immune system through therapeutic delivery centralize around two common themes: the local delivery of biomaterials to affect the surrounding tissue or the systemic delivery of soluble material systems, often aided by context specific cell or tissue targeting strategies. In either case, supramolecular interactions enable control of biomaterial composition, structure, and behavior at the molecular-scale; through rational biomaterial design, realization of next-generation immunotherapeutics and immunotheranostics is therefore made possible. This brief review highlights methods of harnessing macromolecular interaction for immunotherapeutic applications, with an emphasis on modes of drug delivery.